Guatemala's Refugees: Victims and Shapers of Government Policies - Kelly, Deirdre (Tufts Archival Research Center, 2005)
Volume 7, Issue 2. Summer During the past year, Guatemala, along with the rest of troubled Central America, has been thrust to the forefront of the world stage. Yet the international community has been selective in where it directs its attention, tending to emphasize the strategic importance of the region while neglecting the human aspects of Central America's turmoil. In the following article, Deirdre Kelly focuses on the human costs of Guatemala's ongoing civil strife. Kelly argues that the Guatemalan peasants who have sought refuge in neighboring Mexico have significantly affected both the domestic and foreign policies of Guatemala and Mexico. The author's findings suggest that it is time to reevaluate the role of refugees as a policy-determining factor in international affairs.